Glandular Odontogenic-The Multifaceted Cyst of the Jaw: An Unusal Case Report - Singh, Jaya; Singh, Shruti; Singh, Diksha; Chandra, Shaleen; Fatima, Tanveer; Kour, Manjit; Gupta, Nikhil (Archives of Clinical and Medical Case Reports, 2020)
Glandular odontogenic cysts is one of the infrequent neoplasms seen in the oral cavity. They are developmental in origin with unpredictable and aggressive behavior. They are most commonly found in the anterior region of mandible having a predilection for the middle age group. These cysts have striking histologic features even though they have certain overlapping characteristics with other neoplasms. It is very important for us to cognize these unique differentiating features for a conclusive diagnosis. This paper reviews a case of Glandular odontogenic cyst which presented in our department and also elucidates the clinical, radiographical and histological criteria needed to diagnose the same.